Muslim Investors' Behavior in Deciding to Invest in Sharia Shares in the Period 2018-2023: A Systematic Literature Review - Ghofar Taufik; Oman Rusmana (Penerbit Goodwood, 2023)
Purpose: This study is to investigate the factors that influence Muslim investors' decisions to invest in Sharia-compliant shares. This study aims to provide a detailed description of insider investor decision-making behavior. Methodology: Using the Scopus database and Google Scholar, the author analyzed 10 articles published between 2018 and 2023 to map the pattern of behavior of Muslim investors in deciding whether to invest in Sharia shares. Data was collected and reviewed before doing an analysis review, followed by a systematic literature review to support the next study. Results: Findings show that Muslim investors’ decisions in Islamic stock investment are influenced by ethics, motivation, investment patterns, religiosity, expected return, and risk. This study helps investors understand decision-making factors, improve risk perception, and supports Islamic financial institutions and government efforts to develop the Islamic capital market. Conclusions: Based on ten selected studies, Muslim investors in the Islamic capital market are influenced by ethical values, religiosity, motivation, risk, and expected returns. Their decisions reflect a balance between Sharia compliance and rational investment considerations. Limitations: This study has several limitations. First, the systematic review included only ten articles published between 2018 and 2023, which may limit the comprehensiveness of the findings. Second, the selected studies varied in methodology, sample size, and context, which may affect the generalizability of the conclusions. Contributions: This study contributes to understanding Muslim investors’ behavior in Islamic stock investment by highlighting the role of ethics, religiosity, return, and risk in investment decision-making.